A highly conserved iron-sulfur cluster assembly machinery between humans and amoeba dictyostelium discoideum: The characterization of frataxin - Olmos, Justo (2020)
Several biological activities depend on iron–sulfur clusters ([Fe-S]). Even though they are well-known in several organisms their function and metabolic pathway were poorly understood in the majority of the organisms. We propose to use the amoeba Dictyostelium discoideum, as a biological model to study the biosynthesis of [Fe-S] at the molecular, cellular and organism levels. First, we have explored the D. discoideum genome looking for genes corresponding to the subunits that constitute the molecular machinery for Fe-S cluster assembly and, based on the structure of the mammalian supercomplex and amino acid conservation profiles, we inferred the full functionality of the amoeba machinery. After that, we expressed the recombinant mature form of D. discoideum frataxin protein (DdFXN), the kinetic activator of this pathway. We characterized the protein and its conformational stability. DdFXN is monomeric and compact. The analysis of the secondary structure content, calculated using the far-UV CD spectra, was compatible with the data expected for the FXN fold, and near-UV CD spectra were compatible with the data corresponding to a folded protein. In addition, Tryptophan fluorescence indicated that the emission occurs from an apolar environment. However, the conformation of DdFXN is significantly less stable than that of the human FXN, (4.0 vs. 9.0 kcal mol−1, respectively). Based on a sequence analysis and structural models of DdFXN, we investigated key residues involved in the interaction of DdFXN with the supercomplex and the effect of point mutations on the energetics of the DdFXN tertiary structure. More than 10 residues involved in Friedreich’s Ataxia are conserved between the human and DdFXN forms, and a good correlation between mutational effect on the energetics of both proteins were found, suggesting the existence of similar sequence/function/stability relationships. Finally, we integrated this information in an evolutionary context which highlights particular variation patterns between amoeba and humans that may reflect a functional importance of specific protein positions. Moreover, the complete pathway obtained forms a piece of evidence in favor of the hypothesis of a shared and highly conserved [Fe-S] assembly machinery between Human and D. discoideum.